2011
DOI: 10.1063/1.3662176
|View full text |Cite
|
Sign up to set email alerts
|

First principles results on TbAl3(BO3)4: A promising magneto-optical material

Abstract: The electronic and optical properties of TbAl3(BO3)4 are determined using density functional theory. The calculated total magnetic moment of 5.96 μB is close to the expected moment of Tb3+. The frequency dependent dielectric function, refractive index, extinction coefficient, absorption, optical reflectivity, and energy loss function are explained in terms of the transitions between the valence and conduction bands. We find very high Kerr angles for ultraviolet light and potential for extension, even into the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
(51 reference statements)
1
5
0
1
Order By: Relevance
“…17, the total DOS reveals a wide bandgap of HABO with the value of ~ 5 eV, with localized 4f states in the middle of the gap. These results are consistent with the DFT calculations on TbAl 3 (BO 3 ) 4 [30]. The spin up states of Ho 4f are mostly between -6 and -3 eV, while the spin down states have a peak at about -2 eV and also occur near the center of the gap.…”
Section: F Density Function Theory (Dft) Calculationsupporting
confidence: 81%
See 1 more Smart Citation
“…17, the total DOS reveals a wide bandgap of HABO with the value of ~ 5 eV, with localized 4f states in the middle of the gap. These results are consistent with the DFT calculations on TbAl 3 (BO 3 ) 4 [30]. The spin up states of Ho 4f are mostly between -6 and -3 eV, while the spin down states have a peak at about -2 eV and also occur near the center of the gap.…”
Section: F Density Function Theory (Dft) Calculationsupporting
confidence: 81%
“…This suggests that a study of the properties of the isostructural compound RAl 3 (BO 3 ) 4 (RABO) with only 4f electrons on the R site driving the magnetism, would be quite useful to determine the basic physics behind the borate systems. A first-principles calculation on TbAl 3 (BO 3 ) 4 [30] revealed that this class of material has a very promising potential in magneto-optical usage. An experimental study of the TmAl 3 (BO 3 ) 4 [29] system has reported a magnetoelectric polarization changes in a and c directions reach values up to 0.03µC/cm 2 at 7 T with the applied magnetic field along the a axis.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] The combination of high physical characteristics and chemical stability of the borates with huntite structure has long been used as elements of optical and optoelectronic devices, [5][6][7] specifically to add and multiply the laser radiation frequencies. 8,9 Besides, they are observed to have a somewhat unusual structural phase transition between nonpolar phases of trigonal crystal system (from high-temperature R32 (Z ¼ 1) into low-temperature P3 1 21 (Z ¼ 3). The structure with two magnetic ions of different types (3d and 4f ) gives rise to magnetic order at low temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Исследуемые в настоящей работе кристаллы NdFe 3 (BO 3 ) 4 , Nd 0.5 Gd 0.5 Fe 3 (BO 3 ) 4 и Ho 0.75 Nd 0.25 Fe 3 (BO 3 ) 4 относятся к материалам данного типа, о чем свидетельствуют исследования их магнитных, магитоупругих и магнитоэлектрических свойств [3][4][5]. Сочетание физических характеристик и химической стабильности боратов со структурой хантита позволяет использовать их в качестве элементов оптических и оптоэлектронных устройств [6][7][8], в частности, для сложения и умножения частот лазерного излучения [9,10].…”
Section: Introductionunclassified